2021
DOI: 10.1088/1755-1315/679/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of tambaqui (Colossoma macropomum) supplemented with honey prebiotic in stagnant peat ponds

Abstract: This study aims to evaluate the effectiveness of giving honey as a prebiotic in increasing the growth performance of freshwater pomfret (Colossoma macropomum). In this study, honey was mixed into the feed with the method coated at doses of 0.0%, 0.3%, 0.6%, and 0.9%. Fish with an initial body weight of 3-5 g are reared in three ponds with a total of 12 hapa nets measuring 1x1x1 (m3) (40 fish / hapa nets), that is, 4 hapa nets are placed in each pond. Thus, each treatment replication could be represented in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…(Basu, 1993). Recently, Silalahi et al (2021) reported that the administration of honey with a dose of 0.6% is effective in improving the feed conversion ratio, increasing feed efficiency, daily growth rate, body weight gain, and reducing the amount of feed consumption of freshwater pomfret in inundated peat fish ponds.…”
Section: Market Outletmentioning
confidence: 99%
“…(Basu, 1993). Recently, Silalahi et al (2021) reported that the administration of honey with a dose of 0.6% is effective in improving the feed conversion ratio, increasing feed efficiency, daily growth rate, body weight gain, and reducing the amount of feed consumption of freshwater pomfret in inundated peat fish ponds.…”
Section: Market Outletmentioning
confidence: 99%
“…Pemberian madu polen (El-Asely et al, 2014) dan propolis (Azza and Abd-El Rahman, 2009) dapat meningkatkan kinerja pertumbuhan, respons imun, dan resistansi ikan nila (Oreochromis niloticus) terhadap infeksi Aeromonas hydrophila. Pemberian prebiotik madu dosis 0,6% melalui pakan mampu meningkatkan kinerja pertumbuhan ikan bawal air tawar (Colossoma macropomum) (Silalahi et al, 2021). Namun, sejauh ini belum ada data tentang respons ikan gabus (Channa striata) yang diberi suplementasi pakan mengandung madu dan pakan berupa pasta jeroan ikan patin.…”
unclassified